Speculative Child Figures at the End of the (White) World - Ashton, Emily (Journal of Childhood Studies, 2022)
The child-future join is pervasive in childhood studies and popular culture. Instead of disavowing the relation, I consider what might be generated if we “stay with the trouble” of its cocomposition in the making of worlds. To do so, I turn to a zombie child named Melanie from The Girl with All the Gifts to grapple with how the end of the world might not be a cause for mourning, how fiery landscapes can allow for species regeneration, and how viruses might incite counternarratives of community amid contagion.